The evolution of fire management practices in savanna protected areas in South Africa - B.W. van Wilgen (South African Journal of Science)
The history and development of ecologically-based fire management policies in savanna protected areas during the 20th century are reviewed. Research on fire in savannas began in the 1950s, and from the 1980s onwards, managers of savanna protected areas experimented on large scales with different management approaches. New ecological paradigms that embraced variability in space and time, and management goals that broadened from single-species to biodiversity conservation, precipitated significant changes to management approaches in the 1990s. Many lessons have been learnt in the process, allowing for the derivation of general principles regarding both the effects of fire and managerial ability to influence fire regimes on a large scale. Significant challenges remain; these include dealing with increasing CO2 concentrations in the atmosphere, and with interactions between fire and increasing elephant numbers in protected areas. The ability of savanna managers to deal with these challenges in the context of an imperfect understanding will be determined by how well, and how fast, they can learn from experience.